2020
DOI: 10.1080/10872981.2020.1847755
|View full text |Cite
|
Sign up to set email alerts
|

Eight-hour medication-assisted treatment waiver training for opioid use disorder: integration into medical school curriculum

Abstract: Background: The opioid epidemic is a growing problem in the USA. Use of medicationassisted treatment (MAT) has been effective in treating patients with opioid use disorders (OUD) and maintaining sobriety; however, there is a significant shortage of physicians formally trained in MAT. Objective: Wayne State University School of Medicine integrated the 8-hour MAT waiver training into its Internal Medicine clerkship curriculum. The objectives of integrating this into the curriculum were to (1) introduce opioid us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 5 publications
(6 reference statements)
1
32
1
Order By: Relevance
“…A variety of approaches for training medical students on OUD have shown success in short-term survey outcomes, including online training modules, student-tailored DATA-2000 waiver training, small-group discussions, and video-based tutorials. 26 28 In contrast to studies showing positive survey outcomes of educational interventions, we were able to demonstrate effective application of knowledge gained based on improved clinical documentation.…”
Section: Discussioncontrasting
confidence: 87%
“…A variety of approaches for training medical students on OUD have shown success in short-term survey outcomes, including online training modules, student-tailored DATA-2000 waiver training, small-group discussions, and video-based tutorials. 26 28 In contrast to studies showing positive survey outcomes of educational interventions, we were able to demonstrate effective application of knowledge gained based on improved clinical documentation.…”
Section: Discussioncontrasting
confidence: 87%
“…3,6,9 The study is unique in examining the feasibility and impact of completing MAT waiver training during PA student rotations. Three recent studies [11][12][13] from the medical education literature report the positive impact of MAT waiver training on improving medical students' preparation to care for patients with SUD and OUD during clerkships, 12 although training is only 8 hours for medical students compared with 24 hours for PA students. 8 The study affirmed the hypothesis that completing online training during PA student rotations was feasible and would be associated with improved self-assessed competence and positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Themes were ranked according to frequency of occurrence. The major themes were: need more preparation and interaction with materials (9 comments), desire more flexibility in delivery platform (12), and contrasting views about relevance to future practice (5). Table 3 provides typical quotes associated with each theme.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Medical schools are starting to incorporate this into their curriculum through grants or free training programs. Lien et al (2021) found that utilizing the Providers Clinical Support System’s (PCSS) 8-hr online training program allows schools to provide training and assessment for no cost, demonstrated with 300 students in their third year of medical school. The results showed increased confidence and knowledge in OUD and prescribing buprenorphine.…”
Section: Discussionmentioning
confidence: 99%